2010
DOI: 10.1089/apc.2010.0146
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Patterns of Use and the Feasibility of Using Cellular Phones for Clinic Appointment Reminders and Adherence Messages in an Antiretroviral Treatment Clinic, Durban, South Africa

Abstract: In preparation for a proposed intervention at an antiretroviral therapy (ART) clinic in Durban, South Africa, we explored the dynamics and patterns of cellular phone use among this population, in order to ascertain whether clinic contact via patients' cellular phones was a feasible and acceptable modality for appointment reminders and adherence messages. Adults, who were more than 18 years old, ambulatory, and who presented for treatment at the clinic between October-December 2007, were consecutively recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
84
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 7 publications
14
84
1
Order By: Relevance
“…3,18 Data from developing countries have highlighted the impact of mobile technology on communicable diseases, such as tuberculosis, human immunodeficiency virus, and malaria. [19][20][21][22] However, to communication and short message service [SMS]) on chronic disease outcomes in LMIC.…”
Section: Introductionmentioning
confidence: 99%
“…3,18 Data from developing countries have highlighted the impact of mobile technology on communicable diseases, such as tuberculosis, human immunodeficiency virus, and malaria. [19][20][21][22] However, to communication and short message service [SMS]) on chronic disease outcomes in LMIC.…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies conducted in South Africa and other countries have also indicated that mobile phone technology is not only widespread 25 but it is also effective for dealing with psychiatric illness 26,27 and for adherence to ARV therapy. 28 The issue of the possibility of treatment partners becoming too coercive in their approach to adherence is a critical one, given the danger of compromising patient autonomy. However, the approach that our caregiver participants describe where they take an active role in encouraging adherence is probably not unjustified.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an observed effect may be explained in part by the prevalence of cellular phone turnover. Cellular phone turnover has been reported to be common in a semi-urban area in South Africa due to theft or loss (39%) and/or damage (28%) 45 . Of the participants who received text message reminders, 43% (n=23) could not be reached telephonically and 9.3% (n=5) of the numbers no longer existed.…”
Section: Logistical Issuesmentioning
confidence: 99%